Sandalwood Album Oil as a Botanical Therapeutic in Dermatology - Moy, Ronald L. (J Clin Aesthet Dermatol, 2017)
Many skin conditions and diseases are characterized by inflammation, infection, and hyperplasia. Safe and effective topical treatment options that can be used long-term are needed. Traditional botanical medicines, which are often complex mixtures that exert their biological activities via multiple mechanisms of action, are being studied as potential new active ingredients in dermatology. Sandalwood album oil (SAO), also known as East Indian sandalwood oil (EISO), is an essential oil distilled from the Santalum album tree and has demonstrated biological activity as an anti-inflammatory, anti-microbial, and anti-proliferative agent. Sandalwood album oil has also shown promise in clinical trials for treatment of acne, psoriasis, eczema, common warts, and molluscum contagiosum. The favorable safety profile, ease of topical use, and recent availability of pharmaceutical-grade sandalwood album oil support its broader use as the basis of novel therapies in dermatology.